The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1038/ejhg.2011.4
|View full text |Cite
|
Sign up to set email alerts
|

Common variants near TERC are associated with leukocyte telomere length in the Chinese Han population

Abstract: A recent genome-wide association study has identified an association between leukocyte telomere length (LTL) and a locus at 3q26 that includes TERC. In order to evaluate the effects of the SNPs rs12696304 and rs16847897 near TERC in the population of mainland China, we conducted an association study of LTL focusing on these two candidate SNPs in a sample of 4016 Chinese Han individuals. Multiple linear regression analyses were performed to evaluate the association of LTL with each SNP adjusted for age, gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 15 publications
4
56
0
Order By: Relevance
“…Prescott et al replicated previously identified GWAS loci TERC in the Nurses' Health Study but failed to replicate other locus or identify any new loci significant associated with Telomere Length . Shen et al, not surprisingly detected the TERC locus to have significant effect on Leukocyte Telomere Length in Chinese population through unbiased genome screening (Shen et al, 2011); the same two SNPs were found to be associated with Telomere Length as well as longevity in the oldest-old Danes (Soerensen et al, 2011).…”
Section: Telomere Length In the Genomic Eramentioning
confidence: 98%
“…Prescott et al replicated previously identified GWAS loci TERC in the Nurses' Health Study but failed to replicate other locus or identify any new loci significant associated with Telomere Length . Shen et al, not surprisingly detected the TERC locus to have significant effect on Leukocyte Telomere Length in Chinese population through unbiased genome screening (Shen et al, 2011); the same two SNPs were found to be associated with Telomere Length as well as longevity in the oldest-old Danes (Soerensen et al, 2011).…”
Section: Telomere Length In the Genomic Eramentioning
confidence: 98%
“…In the first instance, the significance threshold was determined by the Bonferroni method, which corrects the critical significance level by the number of tests (n) performed (a¼0.05/n), and is commonly used in candidate gene studies. 41 It is recognized that the Bonferroni correction can be overly conservative for non-independent tests. 42 Therefore, we calculated the number of independent tests performed.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…11 Genetic association studies have revealed associations between single-nucleotide polymorphisms (SNPs) in the TERC and TERT genes and TL. [11][12][13][14][15][16][17] Other studies reported associations between SNPs in TERC and POT1 with human longevity, 11,17,18 suggesting that genes regulating TL may influence human longevity.…”
Section: Introductionmentioning
confidence: 99%